#TITLE_ALTERNATIVE# - TRI UTOMO (NIM : 12212044), YANUAR
Study about miscible CO2 EOR at Jatibarang Field has been done since 2005 by PT. Pertamina with Lemigas and ITB. This program will be one of the biggest miscible CO2 flooding in Indonesia with the need of CO2 injection up to 20 mmscfd. To fulfill the need, CO2 is gained and transported from Jatibarang Gas Processing Plant via a 15 km pipeline daily. This study has purpose to get the optimum CO2 transport facility design for this program. Compression system design to keep CO2 in supercritical condition along the flowline becomes the main concern in designing CO2 transport facility. Moreover, the compression system design has to meet the flowrate and injection pressure requirement that can fulfill the Minimum Miscible Pressure (MMP) of 2575 psia. After designing the compression system design and operation pressure along the pipeline, another facilities design such as pipe diameter and material selection, wall thickness, and dehydrator can then be addressed. There are two main scenarios of compression system design that is made. In first scenario, CO2 from source is compressed to reach the maximum operation pressure of pipe, 2000 psia. Meanwhile in second scenario, CO2 from source is compressed to reach minimum pressure needed to keep supercritical condition along the pipe which is 1500 psia. Then these two scenarios are compared by compression power needed and another requirement such as pipe material to get the best scenario. From this study, first scenario is known to be the best scenario. It is then used to get the optimum compressor design, pipe selection and dehydrator design for miscible CO2 EOR program at Jatibarang Field.